Causality between sarcopenia and diabetic neuropathy - Fang, Yi; Yuan, Xiaoqing; Zhang, Qing; Liu, Juan; Yao, Qing; Ye, Xinhua (Frontiers in Endocrinology, 2024)
Background: Past studies have demonstrated that diabetic neuropathy is related to sarcopenia, but the further causal relation is still unclear. We sought to investigate the causal relationship by combining data from cross-sectional and Mendelian randomization (MR) studies.: The genome-wide association studies data were collected from the UK Biobank and the European Working Group on Sarcopenia to conduct a bi-directional two-sample MR study to explore the causality between diabetic neuropathy and relevant clinical traits of sarcopenia, including appendicular lean mass (ALM), walking speed and low hand grip strength. The inverse-variance weighted and various sensitivity analyses were used to obtain MR estimates. We also enrolled a total of 196 Type 2 diabetes patients from April 2021 to April 2024 and divided them into the Distal peripheral neuropathy (DPN) group (n=51) and non-DPN group (n=145) via vibration perception threshold (VPT) and neuropathy deficit score. Logistic regression and ROC curve analysis were used to investigate the relationship between DPN and relevant sarcopenia clinical features. Results: According to a forward MR analysis, decreased walking speed (OR: 0.04, 95% confidence interval (CI): 0.01-0.16; P<0.001) and increased ALM (1.25 [1.05-1.50], P=0.012) had a causal effect on developing diabetic neuropathy. According to reverse MR results, developing diabetic neuropathy had a causal effect on decreased walking speed (0.99 [0.99-1.00], P=0.007) and low grip strength (1.05 [1.02-1.08], P0.001). The cross-sectional study showed that 5-time stand time (P=0.002) and 6meter walking speed (P=0.009) had an inverse association with DPN. Additionally, we discovered that ASMI (P=0.030) and 5-time stand time (P=0.013) were separate risk factors for DPN.The MR study suggested that diabetic neuropathy may have a causality with relevant clinical traits of sarcopenia, and our cross-sectional study further proved that sarcopenia indexes are predictors of diabetic neuropathy.